Occurrence of anti-Neospora caninum antibodies in Brazilian cervids kept in captivity - Tiemann, JCH; Rodrigues, AAR; de Souza, SLP; Duarte, JMB; Gennari, S. M. (Elsevier B.V., 2005)
Neospora caninum is a coccidian parasite that causes disease in captive and domesticated animals and has been found in wild animals such as cervids. Sera from 150 cervids of the genus Mazama, were collected from 31 captive herds and 16 zoos from different Brazilian regions and analyzed by indirect fluorescent antibody test for anti-N. caninum antibodies. Positive reactions were found in 42% (63) of the samples and the titers varied from 50 to 51,200. of the 86 cervids from the captive herds, 38 (44.2%) had anti N. caninum antibodies and of the 64 samples from the zoo, 25 (39.1%) were positive. No significant difference (p > 0.05) was found for the occurrence values observed between the animals from captive herds and zoos as well as within the values documented for each one of the species analyzed. Therefore, the results indicate that the agent is prevalent from cervids in captivity in Brazil. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Neospora caninum; cervids; Brazilian regions